Efektivitas Pendekatan Berbasis STEM (Science, Technology, Engineering, and Mathematics) dalam Pembelajaran Matematika Abad ke-21 - Nur Rarastika; Khairunnisa Nasution; Monalisa Chaira Nainggolan; Dwi Tarisya; Rehan Safira; Isyrofirrahmah Isyrofirrahmah; Elvi Mailani (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2025)
The research aims to examine the effectiveness of the STEM-based approach in 21st-century mathematics learning. The STEM-based approach integrates four main disciplines science, technology, engineering, and mathematics into the learning process to enhance critical thinking and problem-solving skills. The STEM approach is highly relevant to developing 21st-century competencies in mathematics education as both focus on the skills required to address complex and dynamic global challenges, such as critical thinking, problem-solving, creativity, communication, collaboration, and digital literacy. The research method employed is a literature review, analyzing relevant theories and previous studies on the topic. The results indicate that the STEM approach can improve the effectiveness of 21st-century mathematics learning, such as enhancing students' technological development skills, analytical abilities, creativity, innovation, and the ability to express ideas and formulate problems. The STEM approach also stimulates students to meet the demands of 21st-century mathematics learning, which emphasizes critical and problem-solving skills leading to critical, creative, lateral, and systemic thinking abilities.